Nifedipine toxicity is exacerbated by acetyl l-carnitine but alleviated by low-dose ketamine in zebrafish in vivo - Robinson, Bonnie L. (J Appl Toxicol, 2019)
Calcium channel blocker (CCB) poisoning is a common and sometimes life-threatening emergency. Our previous studies have shown that acetyl l-carnitine (ALCAR) prevents cardiotoxicity and developmental toxicity induced by verapamil, a CCB used to treat patients with hypertension. Here, we tested whether toxicities of nifedipine, a dihydropyridine CCB used to treat hypertension, can also be mitigated by co-treatment with ALCAR. In the zebrafish embryos at three different developmental stages, nifedipine induced developmental toxicity with pericardial sac edema in a dose-dependent manner, which were surprisingly exacerbated with ALCAR co-treatment. Even with low-dose nifedipine (5 μm), when the pericardial sac looked normal, ALCAR co-treatment showed pericardial sac edema. We hypothesized that toxicity by nifedipine, a vasodilator, may be prevented by ketamine, a known vasoconstrictor. Nifedipine toxicity in the embryos was effectively prevented by co-treatment with low (subanesthetic) doses (25–100 μm added to the water) of ketamine, although a high dose of ketamine (2 mM added to the water) partially prevented the toxicity.As expected of a CCB, nifedipine either in the presence or absence of ketamine-reduced metabolic reactive oxygen species (ROS), a downstream product of calcium signaling, in the rapidly developing digestive system. However, nifedipine induced ROS in the trunk region that showed significantly stunted growth indicating that the tissues under stress potentially produced pathologic ROS. To the best of our knowledge, these studies for the first time show that nifedipine and the dietary supplement ALCAR together induce adverse effects while providing evidence on the therapeutic efficacy of subanesthetic doses of ketamine against nifedipine toxicity in vivo.